Worth a Closer Look: Raman Spectra of Lead-Pipe Scale - Pasteris, Jill Dill*; Bae, Yeunook; Daniel E. Giammar; Dybing, Sydney N.; Yoder, Claude H.; Juntao Zhao; Yandi Hu (Minerals, 2021)
The identification and characterization of lead-bearing and associated minerals in scales on lead pipes are essential to understanding and predicting the mobilization of lead into drinking water. Despite its long-recognized usefulness in the unambiguous identification of crystalline and amorphous solids, distinguishing between polymorphic phases, and rapid and non-destructive analysis on the micrometer spatial scale, the Raman spectroscopy (RS) technique has been applied only occasionally in the analysis of scales in lead service lines (LSLs). This article illustrates multiple applications of RS not just for the identification of phases, but also compositional and structural characterization of scale materials in harvested lead pipes and experimental pipe-loop/recirculation systems. RS is shown to be a sensitive monitor of these characteristics through analyses on cross-sections of lead pipes, raw interior pipe walls, particulates captured in filters, and scrapings from pipes. RS proves to be especially sensitive to the state of crystallinity of scale phases (important to their solubility) and to the specific chemistry of phases precipitated upon the introduction of orthophosphate to the water system. It can be used effectively alone as well as in conjunction with more standard analytical techniques. By means of fiber-optic probes, RS has potential for in situ, real-time analysis within water-filled pipes.